Finite Element Simulation: Tensile test of rib cortical bone - Mendizabal Dones, Ainhitze (My University, 2010)
Thoracic trauma is the principal causative factor in 30% of road traffic deaths [1]. And when 6 or more ribs are fractured, mortality rate and associated injuries to the head and thorax are increased significantly [2]. This thesis work was carried out to improve the understanding of the mechanical properties of the human rib. These properties are necessary in order to develop realistic finite element models of human chest which are used in the field of vehicle safety. The purpose of this study was to collect values for the rib mechanical properties obtained experimentally. And to compare the values of material properties of human rib cortical bone used in the FE simulation of THUMS with the material properties of human rib cortical bone of PMHS analyzed by Kemper et al. with a tensile test [3]. It has been simulated a tensile test of a specimen of cortical bone of the rib with a FEM in Ls Dyna. The cortical bone has considered a piecewise linear plasticity material and it has been simulated with shell elements. The specimen was loaded at a rate of 5 mm/s (0.5 strains/s). The results of the traction test have been compared with those of Kemper et al. realized on six PMHS. It has been observed that the FE model results are closer to the experimental results if strain rate parameters are not used.
Keywords: Övrig teknisk mekanik; Other engineering mechanics